Prevalence of cervical cytology abnormalities and its correlation with HPV infection among different age groups: Single institution five-year experience - Nina Čamdžić; Arina Brkić; Emina Mameledžija; Mirsad Babić; Mirsad Dorić; Suada Kuskunović-Vlahovljak; Edina Lazović Salčin (Medicinski glasnik, 2025)
Aim: to investigate the prevalence of cervical cytology abnormalities over five years and to correlate it with patient’s age and presence/absence of HPV infection. Methods: Pap findings of 614 women with documented cervical abnormalities and Pap findings of HPV-positive women (regardless of whether the Pap test showed an intraepithelial abnormality) were included in this study. Results: The majority of women included in the study (36.5%) were aged 30-39 years. The most common abnormalities included atypical squamous cells-ASC (47.4%) and low-grade intraepithelial lesions (LSIL)-15.1%. Out of 614 women, 270 (43.9%) were positive for HPV. HR HPV positivity was found in 256 (41.7%). The proportion of HPV infection positivity decreases with age, especially in the two oldest age groups (women older than 60), p=0.03. The analysis showed a higher ratio of Pap smear abnormalities in groups of patients older than 40 years of age (p=0.02). The youngest age group (patients younger than 20 years of age) showed no other lesions than ASC, while women younger than 40 had no SCC on Pap smear. (p<0.01). Out of 256 HR HPV- positive women 42.2% (n=108) showed Pap abnormalities. HR HPV-positive women more commonly had HSIL lesions, but without statistical significance (p>0.05). Conclusion: The results obtained contribute to the knowledge about HPV prevalence and the incidence of squamous cell abnormalities and confirm the necessity for further implementation of HPV vaccination and organized cervical cancer screening program on national level. Keywords: cervical dysplasia, Pap smear, screening
Keywords: cervical dysplasia; Pap smear; screening